PERCEPTIONS AND WILLINGNESS OF VISUALLY IMPAIRED STUDENTS TOWARDS USING TELL IN LEARNING LANGUAGE AT SLB-A YAPTI MAKASSAR - Rahmat J; Abidin Pammu; Ria Rosdiana Jubhari (JURNAL ILMU BUDAYA, 2021)
The aim of this study was to identify the types of technological tools and applications used by students with visual impairment at SLBA-A Yapti Makassar and analyze the students' perception and willingness in using various means of technology in their EFL Classroom. The questionnaires and interviews were used to perform the study methods in which the researcher used Google form that sent to students via WhatsApp feature. Despite the challenge of visual impairment faced by students in integrating technology in the classroom, the results showed that students have positive attitudes about the use of those technology and applications.